Comparative Efficacy of Prostate Tumor Induction Methods in Wistar Rats - Chinenye Mary, Okorochi; Moses Nifemi, Sodeinde; Enoch Chibuike, Okorochi; Adeyinka Samson, Akinyo; Olakunle, Jegede Olushola; Felix Edoiseh, Ehidiamhen; McNelson Nlemchukwu, Dike Ejike; Macpherson Ifeanyi, Ukachukwu; Augustine Ifeanyi, Obiozor; Gerald Ikechi, Eze; et al. (Asian Pacific Journal of Cancer Biology, 2025)
Objectives: This study aims to evaluate and compare the efficacy of three methods for inducing prostate tumors in male Wistar rats: hormonal induction using testosterone propionate, chemical induction with cadmium chloride, and a combination of both agents. The research seeks to enhance understanding of the interactions between environmental and hormonal factors in prostate cancer development. Materials and Methods: Twenty-five male Wistar rats (180-220 grams) were randomly assigned to five groups: a control group (no induction), a low-dose cadmium chloride group (1 mg/kg), a high-dose cadmium chloride group (2 mg/kg), a testosterone propionate group (5 mg/kg), and a combination group (1 mg/kg cadmium chloride + 5 mg/kg testosterone). Each treatment was administered over four weeks, followed by a four-week observation period. Histopathological analyses were conducted on prostate tissues using Hematoxylin and Eosin (H&E) staining to assess tumor characteristics and progression. Results: Histopathological examination revealed that the control group exhibited normal prostate architecture. The low-dose cadmium chloride group showed mild hyperplasia, while the high-dose group displayed significant dysplastic changes. The testosterone propionate group demonstrated hyperplastic and pleomorphic epithelium, indicative of early tumorigenesis. The combination group exhibited the most aggressive tumors, characterized by severely dysplastic epithelium and stromal invasion. Survival rates were notably lower in the combination group, indicating increased health risks associated with dual exposure. Conclusions: The study concludes that the combination of cadmium chloride and testosterone propionate results in a more aggressive tumor phenotype compared to either agent alone, suggesting a synergistic effect in prostate carcinogenesis. These findings underscore the importance of using combined hormonal and chemical induction models to better replicate human prostate cancer for experimental research. Further studies are recommended to explore molecular mechanisms and optimize induction protocols for improved translational relevance in prostate cancer research.